The Influence of Nutritional Counseling on the Nutritional Knowledge and Parenting Patterns of Stunting Mothers - Khotimah, Husnul; Farhat, Yasir; Dewi, Zulfiana; Mas'Odah, Siti (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
One of the most common problems is stunting in toddlers. Astambul District ranked third with an average increase in stunting prevalence of 9,06%. This study to identify the characteristics of stunted toddlers and evaluate the effect of nutritional counseling on mothers’ knowledge and parenting practices. The type of research was a quasi-experimental nonequivalent control group design, the population of 117 stunting clowns was divided into a treatment group (with assistance) and a control group (without assistance). The variables of this research are the knowledge and parenting patterns of mothers of stunting toddlers. Data were collected using questionnaires and interviews. Data analysis used the Wilcoxon Test and Mann Whitney Test.The results of this study show that there are differences in the knowledge and parenting patterns of stunting toddler mothers before and after nutritional counseling in the treatment group and the control group (p<0.05) and there is an influence of nutritional counseling on the knowledge and parenting patterns of stunting toddler mothers in the treatment group and control group. (p<0.05). Nutrition counseling has a positive effect in increasing the knowledge and parenting patterns of stunting mothers. However, treatment with assistance is considered more effective. Suggestions for further research are to involve other nutritional problems, such as malnutrition or babies with low birth weight (LBW).